Students’ Perception on the Use of English Textbook for EFL Learning - Azizah, Siti Nur; Qamariah, Zaitun; Nurliana, Nurliana (Journal of English Language and Education, 2025)
Textbook is a medium that helps teachers plan teaching and learning activities. In other words, it does not take much time to create teaching materials for lessons. In addition, students can participate in different activities depending on what they need to learn. This research aimed to find out the students’ perception on the use of English textbook for EFL Learning in the Islamic Secondary School. This research used a descriptive qualitative approach. Data was collected through semi-structured interviews with 10 students of class VIII, who were randomly selected from MTsN 1 Kota Palangka Raya. The interviews were recorded and transcribed, and the data were analyzed using thematic analysis. This research result showed that students generally had positive perceptions of their English textbook. Almost all students felt motivated to learn if the textbook provided interactive problem exercises and case studies that were relevant to real life.